IMPLEMENTASI ETIKA BISNIS, KONSEP PRODUKSI, EFESIENSI PENGOLAHAN PADA UMKM TERHADAP SISTEM SOSIAL EKONOMI PERSPEKTIF EKONOMI ISLAM - Adinda Thaliya; Muhammad Iqbal Fasa; Suharto Suharto (UIN Mataram, 2021)
This study is aimed at determining how the concept and implementation of Islamic business ethics, concepts of production, and processing efficiency for small businesses (SMEs) toward the socio-economic system. The purpose of this study is to determine how the concept of Islamic business ethics, concepts of production, and processing efficiency. Then how its implementation for small businesses (SMEs) in which the results of this study might be used as a resume of a model for other small businesses (SMEs) concerning Islamic business ethics, concepts good production, and processing efficiency well for the socio-economy. This research was conducted with a qualitative descriptive research method which using literature studies and resumes the results of previous research. The results showed that small businesses (SMEs), namely industry of coffee powder Cap Jempol Super Kedaton, Bandar Lampung has fulfilled the standards principles of Islamic business ethic and through this research it can also be seen that the MSMEs studied has fulfilled the standards of production concepts in Islam and has execute processing efficiency well.